Protopectinase-se from Geotrichumklebahnii: Studies of the adsorption and pectin-solubilization capacity (2017)
Protopectinase SE (PPase-SE) is a polygalacturonase produced by Geotrichumklebahnii with the capacity to liberate pectin through protopectin hydrolysis. The protopectin cleavage is a typical heterogeneous-catalysis reaction whose interaction between the enzyme and the protopectin substrate from lemon albedo along with the release of the pectin-reaction product were the objectives of this investigation. The interaction between PPase-SE and protopectin depended on the particle size and the structure of the substrate as well as on the nature of the buffer. The adsorption kinetics follows, for small particles, a Langmuir isotherm pattern. The reaction exhibited Michaelis-Menten kinetics, giving respective apparent-Km and Vmax values of 30.2 g/l and 57.3 g/l.h. The better results in enzyme adsorption and pectin releasing were obtained with citrate and citrate-phosphate buffers. This report constitutes the first investigation in pectin solubilization involving a model for the substrate-binding mechanism within the pectinase-protopectinase system.